A creative collaboration during the COVID-19 pandemic: an intergenerational initiative. (2nd April 2021) - Pritchard, Fiona
Abstract : Lockdown restrictions signalled an end to in-person interaction and collaboration. However, video conferencing platforms have allowed an opportunity to continue the creative engagement of care home residents. Fiona Pritchard elaborates the results of an intergenerational creative project launched during the pandemic.